The "Eusebian Constantine" - Storch, Rudolph H. (Church history, 1971)
Historians generally have concerned themselves with the reliability of the Vita Constantini of Eusebius, while ignoring an important contribution of the panegyricist, namely, the image of Constantine he projects to his readers. This image, or the “Eusebian Constantine,” involves four major elements: (1) all success and benefit derive from the favor of the divinity; (2) only the pious receive divine favor; (3) the most important indication of divine favor for a pious ruler is military victory; and (4) with the victory secured, divine favor will produce peace and unity for the realm. Constantine, being close to Eusebius, helped to mold his own image which is more than a representation of the first Christian emperor—it is a key to understanding the nature of Eusebius' panegyric as well as his notion of Constantine's relationship with the Christian God.